The effects of the combination of caffeine and a short nap on memory. - Chee, Wei Yan. (2010)
Both a short nap and caffeine are well known excellent countermeasures to sleepiness. In this study we explore the combined treatment of both on aspects of memory to help benefit college students studying for examinations. Sixty well-rested students randomly went through one of six different conditions: 20 min nap and caffeinated coffee (Sleep, Caffeinated), 20 min nap and decaffeinated coffee (Sleep, Decaffeinated), 20 min exercise and caffeinated coffee (Exercise, Caffeinated), 20 min exercise and decaffeinated coffee (Exercise, Decaffeinated), 20 min relaxation time and caffeinated coffee (Control, Caffeinated), 20 min relaxation time and decaffeinated coffee (Control, Decaffeinated). Results showed that the combination of napping and caffeine has an additive effect on memory and caffeine has a greater effect on memory consolidation than on encoding and retrieval.